Pengaruh Kebijakan Dividen terhadap Harga Saham pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Faulia Anggeraini; Windi Triana (Journal on Education, 2023)
The purpose of this study is to determine the effect of the Dividend Payout Ratio (DPR) on stock prices. To determine the effect of Dividend Yield (DY) on Stock Prices. To determine the effect of the Dividend Payout Ratio (DPR) and Dividend Yield (DY) simultaneously on stock prices. This study uses secondary data in the form of company financial reports. Sampling using purposive sampling. Data analysis used the classical assumption test, multiple linear regression test. The population in this study are manufacturing companies in the food and beverage sector which are listed on the Indonesia Stock Exchange for the 2017-2020 period with a total sample of 11 companies. Data processing in this study uses the SPSS Software Program (Statistics Package for the Social Science) 25. Based on the research conducted, it can be concluded that the results of the first hypothesis test show that the Dividend Payout Ratio (X1) has a significant effect on Stock Price (Y) with a tcount value > ttable (2.928 > 1.6838), and a significant value of 0.006 <0.05 . The results of testing the second hypothesis show that dividend yield (X2) has a significant effect on stock price (Y) with tcount > ttable (3.442 > 1.6838), and a significant value of 0.001 <0.05. The results of the third hypothesis test show that the Dividend Payout Ratio (X1) and Dividend Yield (X2) simultaneously have a significant effect on stock prices (Y), with a value of Fcount > Ftable (41,253 > 2,839) and a significant 0.000 <0.05.